2023
DOI: 10.2147/cmar.s385968
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Glycolysis Confers Resistance Against Photon but Not Carbon Ion Irradiation in Human Glioma Cell Lines

Abstract: Purpose Metabolic reprogramming is a key hallmark in various malignancies and poses a challenge in achieving success with various therapies. Enhanced glycolysis is known to confer resistance against photon irradiation while the tumor response to carbon ion irradiation (CII) has not been investigated. This study aimed to investigate the effects of enhanced glycolysis on the response of human glioma cell lines to CII compared to the response to X-rays. Material and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…As the liver plays a vital role in energy metabolism, HCC tumorigenesis is inextricably linked to glycolysis. Previous studies have demonstrated that HCC growth, metastasis, and resistance to treatment are closely associated with glycolytic metabolism ( Park et al, 2021 ; Wang et al, 2022b ; Zhou et al, 2022 ; Dou et al, 2023 ; Vashishta et al, 2023 ). Therefore, the construction of accurate prognostic models utilizing machine learning techniques that incorporate glycolysis-related genes is essential for precise diagnosis, individualized therapy, and the prediction of clinical outcomes in HCC patients ( Toh et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the liver plays a vital role in energy metabolism, HCC tumorigenesis is inextricably linked to glycolysis. Previous studies have demonstrated that HCC growth, metastasis, and resistance to treatment are closely associated with glycolytic metabolism ( Park et al, 2021 ; Wang et al, 2022b ; Zhou et al, 2022 ; Dou et al, 2023 ; Vashishta et al, 2023 ). Therefore, the construction of accurate prognostic models utilizing machine learning techniques that incorporate glycolysis-related genes is essential for precise diagnosis, individualized therapy, and the prediction of clinical outcomes in HCC patients ( Toh et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%